Chitosan-loaded chitosan oligosaccharide nanosheet

By incorporating chitosan into chitosan and performing nanomolecular self-assembly, chitosan-loaded chitosan nanosheets were prepared, which solved the shortcomings of chitosan antifungal and antioxidant activities in the prior art, and achieved significant enhancement of biological activity and extended activity aging.

CN119523878APending Publication Date: 2025-02-28INNER MONGOLIA AGRICULTURAL UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411736397.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

In the prior art, few studies have been conducted on the use of nano-antifungal and antioxidants, and most experiments are performed using a single substance, making it difficult to effectively enhance the antifungal and antioxidant activities of chitosan.

Method used

By incorporating chitosan into chitosan, the hydrogen bond between chitosan and chitosan is weakened under low-temperature alkaline conditions, nanomolecules are self-assembled to prepare chitosan-loaded chitosan nanosheets. This method not only enhances the free radical scavenging ability and antifungal activity of chitosan, but also improves the antioxidant and sustained release effects.

Benefits of technology

It significantly enhances the antioxidant, antifungal and other biological activities of chitosan, extends the activity aging, and shows good bactericidal and antioxidant effects in the agricultural and food industry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The invention discloses a chitosan-loaded chitosan oligosaccharide nanosheet, and relates to the field of nano materials, hydrogen bonds between chitosan and chitosan oligosaccharide molecules are utilized, the hydrogen bond capability is controlled to be weakened under a low-temperature alkaline condition, and chitosan-chitosan oligosaccharide is slowly regenerated under continuous stirring to complete a nano molecule self-assembly process, so that the chitosan-loaded chitosan oligosaccharide nanosheet is prepared. And removing impurities to obtain the chitosan-chitosan oligosaccharide two-dimensional nanosheet with uniform size. The derivative can enhance the free radical scavenging capacity and antifungal activity of chitosan.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of nano materials, in particular to a chitosan-loaded chitosan oligosaccharide nanosheet. Background Art

[0002] In the prior art, there are few reports on the use of nano antifungal agents and antioxidants, and most of them use a single substance to test the antifungal and antioxidant effects. Therefore, it is a new direction to develop new antifungal agents and antioxidants by simply modifying natural polymer compounds or preparing them into nano preparations, and conducting in-depth biological activity studies on them. Data show that the new nano antifungal agents and antioxidants developed are not only more effective than traditional antifungal agents and antioxidants, but also have fewer toxic and side effects and lower development costs.

[0003] Chitosan is a natural high molecular polymer with great potential, and nano-chitosan is a new type of carrier for effectively delivering functional groups and trace drugs. Chitosan oligosaccharides are prepared from chitosan and have good biocompatibility and antifungal and antioxidant capabilities. Because their molecular structure contains active hydroxyl (-OH) and amino (-NH2), they can be modified and modified to form derivatives with different structures and functions. Summary of the invention

[0004] The purpose of the present invention is to provide a chitosan-loaded chitosan oligosaccharide nanosheet, wherein the derivative can enhance the free radical scavenging ability and antifungal activity of chitosan itself.

[0005] The present invention adopts the following technical solution:

[0006] The invention provides a chitosan-loaded chitosan oligosaccharide nanosheet. The preparation method is as follows: dissolving chitosan powder with a molecular weight of 20.0-30.0 kDa in a low-temperature alkali-urea aqueous solution, then adding chitosan oligosaccharide, adding a poor solvent after the chitosan oligosaccharide is dissolved to precipitate the chitosan-loaded chitosan oligosaccharide nanosheet, and the solution becomes a suspension; then, centrifuging the suspension to separate solid nanosheets; washing the separated nanosheets on a filter membrane with a poor solvent to remove alkali-urea; and finally drying the separated nanosheets to obtain the chitosan-loaded chitosan oligosaccharide nanosheets.

[0007] Furthermore, the alkali used in the alkali-urea aqueous solution is selected from one or a mixture of NaOH, KOH, and LiOH; and the low temperature range of the alkali-urea aqueous solution is 0-24°C.

[0008] Furthermore, the poor solvent is a mixture of one or more of alcohols, ketones, esters, furans, and pyridines.

[0010] Furthermore, the drying temperature is 40-80°C.

[0011] The beneficial effects of the present invention are as follows: the present invention provides a chitosan-loaded chitosan oligosaccharide nanosheet, which utilizes the hydrogen bond between chitosan and chitosan oligosaccharide molecules, controls the weakening of the hydrogen bond capacity under low temperature alkaline conditions, and under continuous stirring, chitosan-chitosan oligosaccharide is slowly regenerated to complete the nanomolecular self-assembly process, and obtains chitosan-chitosan oligosaccharide two-dimensional nanosheets of uniform size after impurity removal. The thickness of the nanosheet is below 50nm, and the length is between 100nm-10μm. The derivative can enhance the free radical scavenging ability and antifungal activity of chitosan itself. In addition, the chitosan-chitosan oligosaccharide two-dimensional nanosheet also has biological activities such as anti-plant pathogenic fungi, and can be applied to fungicides, antioxidants, etc. in the agricultural field and the food industry. The chitosan-loaded chitosan oligosaccharide nanosheet significantly enhances the unique anti-oxidation, antifungal and other biological activities of chitosan itself, while increasing the sustained release effect and prolonging the active time. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 It is the molecular formula of the chitosan-loaded chitosan oligosaccharide nanosheets of the present invention.

[0013] Figure 2 The schematic diagram is a structural diagram of chitosan-loaded chitosan oligosaccharide nanosheets of the present invention.

[0014] Figure 3 This is the infrared spectrum of the chitosan nanosheet of the present invention.

[0015] Figure 4 It is the infrared spectrum of chitosan oligosaccharide of the present invention.

[0016] Figure 5 This is the infrared spectrum of the chitosan-loaded chitosan oligosaccharide nanosheets of the present invention.

[0017] Figure 6 This is a scanning electron microscope image of the chitosan nanosheets prepared in Example 1 of the present invention.

[0018] Figure 7 This is a scanning electron microscope image of the chitosan-loaded chitosan oligosaccharide nanosheets prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0019] In order to make those skilled in the art better understand the technical solution of the present invention, the present invention will be further described in detail in conjunction with specific embodiments. The following description is only used to illustrate the technical solution of the present invention but not to limit it. The experimental methods used in the embodiments are conventional methods unless otherwise specified. The materials and reagents used can be obtained from commercial sources unless otherwise specified. Chitosan (Mw = 20.0-30.0 kDa) was purchased from Qingdao Yunzhou Biotechnology Co., Ltd., DD> 90%; chitosan oligosaccharide (Mw = 1.0-4.0 kDa).

[0020] Example 1

[0021] Prepare low-temperature alkali-urea aqueous solution: Take 15.0g NaOH and 15.0g urea and dissolve them in 300mL water to prepare alkali-urea aqueous solution, and precool the prepared alkali-urea aqueous solution in an ice water bath to reduce the system temperature to 0°C.

[0022] Take chitosan powder with a molecular weight of 20.0-30.0kDa and a mass of 5.0g and dissolve it in 300mL of alkali-urea aqueous solution, stir until the solution is transparent, the low temperature alkali-urea aqueous solution is used to weaken the hydrogen bonds between chitosan molecules, the reaction amount is based on the reaction phenomenon, and the chitosan can be fully dissolved; then add 5.0g of chitosan oligosaccharide and stir until the solution is transparent, this is to allow the chitosan oligosaccharide to be fully dissolved in the system. Then add 500mL of anhydrous ethanol (poor solvent) to precipitate chitosan-loaded chitosan oligosaccharide nanosheets. The purpose of anhydrous ethanol is to change the polarity of the reaction system. When the input amount of anhydrous ethanol is greater than the input amount of water in the reaction system, the polarity of the reaction system changes, and the reaction phenomenon shows that the solution changes from clear and transparent to a yellow-white turbid suspension; then, the suspension is centrifuged to separate solid nanosheets; the separated nanosheets are repeatedly rinsed with anhydrous ethanol (poor solvent) on a 0.22μm filter membrane to remove alkali-urea. The pH value of the filtrate is tested with a pH meter, and the pH value is between 7.0 and 8.0. The filtrate is dried at a temperature of 40-80° C. to obtain a yellow-brown or brown powder, namely, chitosan-loaded chitosan oligosaccharide nanosheets.

[0023] Supplementary explanation is as follows: In the present invention, the alkali used in the alkali-urea aqueous solution can be selected from one of NaOH, KOH, LiOH or a mixture thereof. The low temperature range of the alkali-urea aqueous solution is 0-24°C. The lower the temperature, the weaker the hydrogen bonding effect between chitosan molecules. 0°C is the optimum temperature for weakening hydrogen bonding.

[0024] In the present invention, the poor solvent can be a mixture of one or more alcohols, ketones, esters, furans, and pyridines. Specifically, anhydrous ethanol and methanol can be used for alcohols; acetone can be used for ketones; ethyl acetate can be used for esters; tetrahydrofuran can be used for furans; and pyridine can be used for pyridines. The standard for the amount of the poor solvent used to dissolve chitosan is that the amount used to evenly disperse chitosan in the solvent is sufficient, and the reaction phenomenon is a yellow-white suspension.

[0025] Figure 1 It is the molecular formula of the chitosan-loaded chitosan oligosaccharide nanosheets of the present invention. Figure 2 The schematic diagram is a structural diagram of chitosan-loaded chitosan oligosaccharide nanosheets of the present invention. Figure 3 The infrared spectrum of the chitosan nanosheet of the present invention is shown in FIG. -1): 3600-3200, 3000-2800, 1750-1550, 1550-1450, 1100-900. Figure 4 The infrared spectrum of chitosan oligosaccharide of the present invention is shown in FIG. -1 ): 3600-3200, 3000-2800, 1750-1550, 1550-1450, 1100-900. Figure 5 The infrared spectrum of chitosan-loaded chitosan oligosaccharide nanosheets of the present invention is shown in Figure 1. -1 ): 3600-3200, 3000-2800, 1750-1550, 1550-1450, 1100-900.

[0026] from Figure 3 It can be seen that the -1 The characteristic absorption peaks of OH and NH of chitosan nanosheets are located at 3000-2800cm -1 The saturated -CH stretching vibration absorption peak is located at 1750-1450cm -1 The characteristic absorption peak of -NH2 is at 1100-900cm -1 The absorption peak is the saturated -CH deformation vibration.

[0027] from Figure 4 It can be seen that the -1 The characteristic absorption peaks of OH and NH of chitosan oligosaccharide are located at 3000-2800cm -1 The saturated -CH stretching vibration absorption peak is located at 1750-1450cm -1 The characteristic absorption peak of -NH2 is located at 1100-900cm -1 The absorption peak is the saturated -CH deformation vibration.

[0028] from Figure 5 It can be seen that the -1 The characteristic absorption peaks of OH and NH of chitosan-loaded chitosan oligosaccharide nanosheets are located at 3000-2800cm -1 The saturated -CH stretching vibration absorption peak is located at 1750-1450cm -1 The characteristic absorption peak of -NH2 is at 1100-900cm -1 The absorption peak is the saturated -CH deformation vibration.

[0029] pass Figure 3 , Figure 4 and Figure 5 The comparison, Figure 3 and Figure 5 The absorption peak of chitosan is red-shifted as a whole, which originates from the quantum size effect. As chitosan is transformed into a nano dosage form, its size decreases, making the quantum size effect significant. This effect causes the energy gap to widen, and the width between the molecular orbital energy levels occupied by electrons and the unoccupied molecular orbital energy levels increases. However, as the particle size decreases, the internal stress inside the particles will also increase. This increase in internal stress will lead to changes in the band structure, increased overlap of electron wave functions, and as a result, narrower band gaps and energy level spacings. This change will lead to a decrease in the energy required for electrons to transition from low energy levels to high energy levels, thereby causing the absorption band and absorption edge of the infrared spectrum to move toward low frequencies (i.e., long wavelengths or red shifts). After the chitosan molecules are transformed into nanometer levels, the infrared light absorption band shifts toward the long-wave direction as a whole. This further demonstrates the successful preparation of chitosan-loaded chitosan oligosaccharide nanosheets.

[0030] Figure 6 This is a scanning electron microscope image of the chitosan nanosheet prepared in Example 1 of the present invention, and its characteristic sizes from left to right are: 10μm, 1μm, 500nm. Figure 6 It can be seen from the figure (a) that the nano-chitosan presents a smooth flaky structure at a size of 10 μm, and from the figures (b) and (c) respectively, it can be seen that the nano-chitosan still has a clear lamella structure at a size of 1 μm and 500 nm, with a lamella thickness of less than 50 nm and a length of less than 10 μm.

[0031] Figure 7 This is a scanning electron microscope image of chitosan-loaded chitosan oligosaccharide nanosheets prepared in Example 1 of the present invention, and its characteristic sizes from left to right are: 10 μm, 1 μm, and 500 nm. Figure 7 It can be seen that the surface of the nano-chitosan after loading chitosan oligosaccharide in (a) is obviously rough at a size of 10 μm, but still maintains a flaky structure. In (b) and (c), it can be seen that the chitosan-loaded chitosan oligosaccharide nanosheets fill and wrap the interlamellar gaps relative to small molecule particles at sizes of 1 μm and 500 nm, with a lamella thickness of less than 50 nm and a length of less than 10 μm.

[0032] Example 2

[0033] Prepare low-temperature alkali-urea aqueous solution: Take 5.0 g NaOH and 5.0 g urea and dissolve them in 100 mL water to prepare alkali-urea aqueous solution, and precool the prepared alkali-urea aqueous solution in an ice water bath to reduce the system temperature to 0°C.

[0034] Take chitosan powder with a molecular weight of 20.0-30.0kDa and a mass of 1.0g and dissolve it in 100mL of low-temperature alkali-urea aqueous solution, stir until the solution is transparent; then add 1.0g of chitosan oligosaccharide and stir until the solution is transparent. Then add 200mL of anhydrous ethanol (poor solvent) to precipitate chitosan-loaded chitosan oligosaccharide nanosheets, and the solution changes from clear and transparent to a yellow-white turbid suspension; then, centrifuge the suspension to separate solid nanosheets; repeatedly rinse the separated nanosheets with anhydrous ethanol (poor solvent) on a 0.22μm filter membrane to remove alkali-urea. Use a pH meter to test the pH value of the filtrate, and the pH value can be between 7.0-8.0. Dry at a temperature of 40-80℃ to obtain a yellow-brown or brown powder, i.e., chitosan-loaded chitosan oligosaccharide nanosheets.

[0035] Example 3

[0036] Prepare low-temperature alkali-urea aqueous solution: Take 25.0 g NaOH and 25.0 g urea and dissolve them in 500 mL water to prepare alkali-urea aqueous solution, and precool the prepared alkali-urea aqueous solution in an ice water bath to reduce the system temperature to 0°C.

[0037] Take chitosan powder with a molecular weight of 20.0-30.0kDa and a mass of 10.0g and dissolve it in 500mL of low-temperature alkali-urea aqueous solution, stir until the solution is transparent; then add 10.0g chitosan oligosaccharide, stir until the solution is transparent, then add 1000mL of anhydrous ethanol (poor solvent) to precipitate chitosan-loaded chitosan oligosaccharide nanosheets, and the solution changes from clear and transparent to a yellow-white turbid suspension; then, centrifuge the suspension to separate solid nanosheets; repeatedly rinse the separated nanosheets with anhydrous ethanol (poor solvent) on a 0.22μm filter membrane to remove alkali-urea. Use a pH meter to test the pH value of the filtrate, and the pH value is between 7.0-8.0. Dry at a temperature of 40-80℃ to obtain a yellow-brown or brown powder, i.e., chitosan-loaded chitosan oligosaccharide nanosheets.

[0038] The free radical scavenging test is as follows:

[0039] Hydroxyl radical scavenging ability: The ·OH in this test is generated by the EDTANa2-Fe(II)-H2O2 system. Safranin O can be uniquely locked by ·OH, causing it to fade. The ·OH content can be measured by colorimetry based on the degree of fading.

[0040] ① Prepare phosphate buffer solution with pH = 7.4: Accurately weigh 5.2887g NaH2PO4·2H2O and 41.58g Na2HPO4·12H2O, add distilled water to make up to 1000mL, shake well, and store for later use.

[0041] ②Prepare Safranin O solution: Accurately weigh 36 mg of Safranin O, dissolve it in phosphate buffer solution, make up to 100 mL, shake well, and store for later use.

[0042] ③Prepare EDTA-Fe solution: accurately weigh 55.60 mg FeSO4 and 0.1489 g EDTA-Na2, mix and dissolve, dilute to 100 mL with distilled water, shake well, and store for later use.

[0043] ④Prepare 3% H2O2 solution: measure 5mL H2O2, use buffer solution as solvent, make up to 50mL, shake well, and store in dark place for later use.

[0044] ⑤ Accurately weigh 62.5 mg of L-ascorbic acid (Vc) and the sample to be tested (NMCS, COS, COSNMCS), and dilute to 25 mL with phosphate buffer solution. The reaction system is shown in Table 1.

[0045] Table 1

[0046] The blank group was added with 2.0 mL of water, and the control group was added with 2.0 mL of water and 4.0 mL of phosphate buffer solution (instead of H2O2), and the absorbance value A was measured at a wavelength of λ=600 nm.

[0047] Calculation formula:

[0048] Where, E—clearance capacity, %; A sample , A blank , A control —Absorbance value of sample, absorbance value of blank group, absorbance value of control group.

[0049] Superoxide anion scavenging ability: The superoxide anion (O2 - ) scavenging ability method. ① Prepare Tris-HCl buffer solution: accurately weigh 1.9382g Tris and 0.8mL concentrated hydrochloric acid, add water to 1000mL, shake well, and save for later use; ② Accurately weigh 36.57mg NADH, 24.53mg NBT, and 1.84mg PMS, respectively, and prepare to 100mL with buffer solution, and save for later use. ③ Accurately weigh 62.5mg sample and prepare to 25mL with buffer solution. The reaction system is shown in Table 2.

[0050] Table 2

[0051] The control group was added with 3.0 mL of Tris-HCl buffer solution, and the blank group was added with 4.0 mL of Tris-HCl buffer solution, 1.0 mL of NBT solution, and 1.0 mL of PMS solution. The absorbance value A was measured at a wavelength of λ=560 nm.

[0052] Calculation formula:

[0053] Where, E—clearance capacity, %; A sample , A control —Absorbance value of sample and control group.

[0054] DPPH free radical scavenging ability: Accurately weigh 7.1 mg DPPH and dissolve it in anhydrous ethanol, dilute to 500 mL, shake well, and save for later use. Prepare a sample solution of a certain concentration, and the reaction system is shown in Table 3.

[0055] Table 3

[0056] After measuring the absorbance value A1 at wavelength λ = 517 nm, 4.0 mL of anhydrous ethanol was added, and the absorbance value A2 was measured at wavelength λ = 517 nm. 4.0 mL of DPPH solution and 1.0 mL of distilled water were added to the blank group.

[0057] Calculation formula:

[0058] Wherein, E is the clearance capacity, %; A1, A2, A0 are the first absorbance value, the second absorbance value, and the absorbance value of the blank group.

[0059] Reducing ability: Prepare phosphate buffer solution: weigh 24.96g NaH2PO4·2H2O and 14.33g Na2HPO4·12H2O, add distilled water to 1000mL, shake well, and save for later use. Accurately weigh 62.5mg of the sample to be tested, and dilute to 25mL with phosphate buffer solution. The reaction system is shown in Table 4.

[0060] Table 4

[0061] The absorbance value A is measured at a wavelength of λ=700nm. The greater the absorbance, the stronger the reducing ability.

[0062] The antifungal testing process is as follows:

[0063] Place the tested bacteria in a biosafety cabinet for activation, use an inoculation needle to intercept part of the colony on the slope, and inoculate it on the PDA medium. Check the growth of the bacteria after 3 days. If it is in a non-contaminated state, continue to culture. Preparation method of PDA medium: Peel 100g of potatoes, put them into 500mL of distilled water and boil for about 30 minutes. Then filter the potato solution, make up the required filtrate with distilled water, and add 15g of agar and 20g of glucose. After the mixture is packaged and sterilized, it is potato glucose agar (PDA) medium. Dissolve NMCS, COS, and COS-NMCS in distilled water to prepare a starting concentration of 20mg·mL -1 The sample solution to be tested. Add a certain amount of the sample solution to the sterilized PDA medium, shake well, prepare the medium with drug content of 2.0mg / mL, 1.0mg / mL, 0.5mg / mL, 0.25mg / mL, 0.125mg / mL, and 0.0625mg / mL, and pour it into a culture dish (9cm in diameter). Three parallel experiments were performed for each sample. Using distilled water as the negative control, inoculate fungal plugs (5mm) on each culture dish. After culturing at 28°C for 48h, measure the colony diameter, and calculate the antibacterial rate according to the following formula:

[0064] E(%)=(Φ a -Φ b / Φ a -5)×100%.

[0065] Among them, Φ a is the mycelial growth diameter of the negative control medium, Φ b is the diameter of mycelial growth in the sample culture medium.

[0066] The free radical scavenging test results are analyzed as follows:

[0067] Table 5. Statistics of hydroxyl radical scavenging ability of chitosan-loaded chitosan oligosaccharide nanosheets.

[0068] Table 6. Statistical table of superoxide anion scavenging ability of chitosan-loaded chitosan oligosaccharide nanosheets.

[0069] Table 7. Statistics of DPPH free radical scavenging ability of chitosan-loaded chitosan oligosaccharide nanosheets.

[0070] Table 8. Statistical table of reducing ability of chitosan-loaded chitosan oligosaccharide nanosheets.

[0071] In Table 5, Table 6, Table 7 and Table 8, chitosan-loaded chitosan oligosaccharide nanosheets all have certain free radical scavenging ability. In Table 5, the hydroxyl radical scavenging ability of chitosan-loaded chitosan oligosaccharide nanosheets, with Vc as the positive control, COS-NMCS has a higher clearance rate than all drug controls at 0.1 and 0.2 mg / mL, and the highest can reach 13.76%, exceeding the positive control Vc by 4.42%. As the concentration increases, the clearance rate gradually decreases below the positive control Vc, but it is still better than the synthetic precursors NMCS and COS at the highest concentration, and the clearance rate can reach 37.31% at a concentration of 0.5 mg / mL.

[0072] In Table 6, the superoxide anion scavenging ability of chitosan-loaded chitosan oligosaccharide nanosheets, with Vc as the positive control, the clearance rate of COS-NMCS increased with the increase of concentration, but did not show a superior scavenging ability than the positive control Vc. The overall clearance rate was only higher than that of the synthetic precursor NMCS, and the clearance rate was 21.92% at a concentration of 0.5 mg / mL.

[0073] In Table 7, the DPPH radical scavenging ability of chitosan-loaded chitosan oligosaccharide nanosheets, with Vc as the positive control, the scavenging rate of COS-NMCS increased with the increase of concentration, but did not show a higher scavenging ability than other control groups. The overall scavenging rate was low, and the scavenging rate was 60.42% at a concentration of 0.5 mg / mL.

[0074] In Table 8, the reducing capacity of chitosan-loaded oligosaccharide nanosheets, the reducing capacity of COS-NMCS increases with the increase of concentration, and the overall reducing capacity is higher than that of all control groups, and the reducing capacity of 0.5 mg / mL concentration can reach 0.192 Abs. In the four tables of free radical scavenging capacity, chitosan-loaded oligosaccharide nanosheets have good hydroxyl radical scavenging and reducing capacity, which is significantly higher than that of oligosaccharide and nano-chitosan itself, indicating that chitosan-loaded oligosaccharide nanosheets have certain antioxidant capacity in vitro.

[0075] The antifungal test results are analyzed as follows:

[0076] Table 9. Statistical table of inhibition rate of wheat sheath blight by chitosan-loaded oligosaccharide nanosheets.

[0077] Table 10. Statistical table of inhibition rate of wheat Gibberella by chitosan-loaded oligosaccharide nanosheets.

[0078] Table 11. Statistical table of inhibition rate of pepper phytophthora by chitosan-loaded oligochitosan nanosheets.

[0079] Table 12. Statistical table of inhibition rate of tomato early blight by chitosan-loaded chitosan oligosaccharide nanosheets.

[0080] Table 13. Statistical table of inhibition rate of Botrytis cinerea by chitosan-loaded oligosaccharide nanosheets.

[0081] Table 14. Statistical table of the inhibition rate of sweet potato intercropping fungus by chitosan-loaded chitosan oligosaccharide nanosheets.

[0082] In Tables 9-14, the antibacterial rate of chitosan-loaded chitosan oligosaccharide nanosheets increases with the increase of concentration, showing a good linear relationship.

[0083] In the inhibition rate of wheat leaf blast fungus on chitosan-loaded oligosaccharide nanosheets in Table 9, the overall inhibition rate of COS-NMCS was better than that of all control groups. At a concentration of 2.0 mg / mL, the inhibition rate reached the highest, which was 46.60%.

[0084] In Table 10, the inhibition rate of chitosan-loaded oligochitosan nanosheets on wheat Gibberella, the overall inhibition rate of COS-NMCS was good. At a concentration of 2.0 mg / mL, the inhibition rate could reach 48.31%, but it was 0.92% lower than that of the synthetic precursor COS.

[0085] In Table 11, the inhibition rate of chitosan-loaded oligosaccharide nanosheets against pepper phytophthora, the overall inhibition rate of COS-NMCS was better than that of all control groups, and the inhibition rate reached the highest at a concentration of 2.0 mg / mL, which was 97.72%. In Table 8, the inhibition rate of chitosan-loaded oligosaccharide nanosheets against tomato phytophthora, the overall inhibition rate of COS-NMCS was good, and the inhibition rate could reach 48.30% at a concentration of 2.0 mg / mL, but it was far inferior to the inhibition rate of the synthetic precursor COS.

[0086] In the inhibition rate of Botrytis cinerea on chitosan-loaded oligochitosan nanosheets in Table 13, the overall inhibition rate of COS-NMCS was better than that of all control groups. At a concentration of 2.0 mg / mL, the inhibition rate reached the highest level, which was 95.01%.

[0087] In Table 14, the inhibition rate of sweet potato intercropping fungus by chitosan-loaded chitosan oligosaccharide nanosheets, the overall inhibition rate of COS-NMCS was lower than that of all control groups, and at a concentration of 2.0 mg / mL, the inhibition rate could only reach 34.08%. It can be seen from the six tables of fungal inhibition rates that chitosan-loaded chitosan oligosaccharide nanosheets have a good inhibitory effect on pepper phytophthora and botrytis cinerea, which is higher than chitosan oligosaccharides and nano-chitosan themselves, and can be used as a good plant antifungal agent.

[0088] The above embodiments are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation methods. For those of ordinary skill in the art, other different forms of changes can be made based on the above description. And the obvious changes derived from this belong to the scope of protection of the present invention. Finally, it should be noted that the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

Claims

1. A chitosan-loaded chitosan oligosaccharide nanosheet, characterized in that: The preparation method is as follows: chitosan powder with a molecular weight of 20.0-30.0 kDa is dissolved in a low-temperature alkali-urea aqueous solution, and then chitosan oligosaccharide is added. After the chitosan oligosaccharide is dissolved, a poor solvent is added to precipitate chitosan-loaded chitosan oligosaccharide nanosheets, and the solution becomes a suspension; then, the suspension is centrifuged to separate solid nanosheets; the separated nanosheets are washed on a filter membrane with a poor solvent to remove alkali-urea; and finally, the separated nanosheets are dried to obtain chitosan-loaded chitosan oligosaccharide nanosheets.

2. The chitosan-loaded chitosan oligosaccharide nanosheet according to claim 1, characterized in that: The alkali used in the alkali-urea aqueous solution is selected from one of NaOH, KOH, LiOH or a mixture thereof; the low temperature range of the alkali-urea aqueous solution is 0-24°C.

3. The chitosan-loaded chitosan oligosaccharide nanosheet according to claim 1, characterized in that: The poor solvent is a mixture of one or more of alcohols, ketones, esters, furans and pyridines.

4. The chitosan-loaded chitosan oligosaccharide nanosheet according to claim 1, characterized in that: The drying temperature is 40-80℃.

Citation Information

Patent Citations

  • Preparation method of chitosan nanosheet

    CN112745518A

  • Preparation method of universal two-dimensional mesoporous nitrogen-doped carbon composite material

    CN117049502A

  • KR20240006895A